Effects of non-isotropic blockage on a tidal turbine modeled with the Actuator-Line method (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Blockage effects are a consequence of the interaction between a body and the surrounding boundaries in a constrained flow. For the case of tidal rotors, global blockage (β) is usually defined bythe ratio between the swept area of the rotor and the cross-sectional area of a channel. Increasingblockage tends to increase the limits of power extraction (Garrett and Cummins, 2007), as well asthrust on a rotor through an attendant increase of through-rotor mass flow. While these observations have been studied and demonstrated for isotropic blockage effects (e.g., Zilic de Arcos et al.2020, Bahaj 2007 , Mikkelsen 2002), questions remain regarding the validity of such assumptionsfor non-isotropic blockage in channels with, e.g., rectangular cross-sections with varying aspectratios.In this work, we will use CFD simulations to analyze the effect of non-isotropic blockage on atidal rotor. The study aims to explore these effects using an Actuator-Line representation of anaxial-flow rotor, simulated under different blockage ratios (1 %, 5 %, 10%, and 19.7 %), aspectratios (0.25, 0.5, 0.75, and 1), and tip speed ratios (4, 5, 6, and 7). A total of 64 cases will beconsidered. For each simulated case, the power, thrust, and spanwise force distributions will beextracted as functions of time, and used to understand the effect of blockage on the performanceof tidal rotors.Our preliminary results, in agreement with existing literature, indicate that blockage affectswake development, as seen in Figure , along with power and thrust. These results, for a constantaspect ratio, show power increases up to 26 % for a blockage of 20 %. The bulk of the simulationmatrix, including the different aspect ratios, is currently under production and is expected to beready before the paper submission deadline. ReferencesGarrett, C., Cummins, P. (2007). The efficiency of a turbine in a tidal channel. Journal of fluidmechanics, 588, 243-251.Zilic de Arcos, F., Tampier, G., Vogel, C. R. (2020). Numerical analysis of blockage correctionmethods for tidal turbines. Journal of Ocean Engineering and Marine Energy, 6, 183-197Bahaj, A. S., Molland, A. F., Chaplin, J. R., Batten, W. M. J. (2007). Power and thrust measurements of marine current turbines under various hydrodynamic flow conditions in a cavitationtunnel and a towing tank. Renewable energy, 32(3), 407-426.Mikkelsen, R., Sørensen, J. N. (2002). Modelling of wind turbine blockage. In 15th IEAsymposium on the aerodynamics of wind turbines, FOI Swedish Defence Research Agency.